PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA ULAR TANGGA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD NEGERI 060923 - Rina Dwi Nurvita Malau; Sutarini; Umar Darwis; Dara Fitrah Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of implementing the Problem-Based Learning (PBL) model using the snakes and ladders model on students' critical thinking skills in the Indonesian language subject in fourth-grade students at Medan Amplas Public Elementary School 060923. This study employed a quasi-experimental design with a nonequivalent control group design. The subjects consisted of two classes: 18 students in the experimental class, Class IV C, taught using the PBL model using the snakes and ladders model, and 18 students in the control class, taught using the PBL model without the snakes and ladders model. The total number of students was 36. The research instrument was a critical thinking ability test administered via pretest and posttest. Data were analyzed using normality, homogeneity, and an independent sample t-test. The results showed a significant effect on students' critical thinking skills after implementing the PBL model using the snakes and ladders model. The average posttest score for the experimental class was 78.44, while the average posttest score for the control class was 69.55, with a significance level of 0.000 <0.05. The pretest-posttest score increase in the experimental class was 17.167 points, higher than the 10.444 points increase in the control class. Thus, it can be concluded that the implementation of the Problem-Based Learning model with the snakes and ladders model significantly improved students' critical thinking skills in Indonesian language learning. The snakes and ladders model made the learning process more engaging, interactive, and meaningful, thereby fostering student motivation and active involvement in the problem-solving process.